2022
DOI: 10.1186/s41983-022-00511-8
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the general population towards migraine in Jeddah, Saudi Arabia

Abstract: Background Migraine is a chronic episodic neurological disorder characterized by a myriad of neurological symptoms including multi-phase attacks of headache, photophobia, phonophobia, and dizziness. To the best of our knowledge, there are no studies conducted about the public perception and attitudes towards migraine in Saudi Arabia. This study aims to determine the public perception and attitudes towards migraine in Jeddah, Saudi Arabia. This cross-sectional study was conducted during the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, 83.1% identified unilateral headache as a main symptom of migraine, and the majority of participants knew about migraine treatment. In Saudi Arabia [ 9 ], 87.3% of their respondents correlate unilateral headaches with migraine, while half of them consider migraine to equally affect both men and women. Additionally, around 51.2% do not know about migraine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 83.1% identified unilateral headache as a main symptom of migraine, and the majority of participants knew about migraine treatment. In Saudi Arabia [ 9 ], 87.3% of their respondents correlate unilateral headaches with migraine, while half of them consider migraine to equally affect both men and women. Additionally, around 51.2% do not know about migraine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They can be seen more quickly in private clinics and hospitals. However, as a result of the self-referral system used in most private hospitals, patients decide which specialty they need to visit and, presumably because of poor awareness of migraine features [ 22 ], many patients access other specialties (including ear nose and throat, ophthalmology, vascular surgery, neurosurgery, gastroenterology, physiotherapy, and alternative medicine) before finally seeing a neurologist or headache specialist.…”
Section: Barriers To Diagnosismentioning
confidence: 99%
“…A migraine is a chronic neurological disorder that affects millions around the world every day and it is experienced by many individuals at some point in their lives [1][2][3][4]. In 2020, migraines were the second leading cause of disability globally [2], and it is the third most prevalent condition among individuals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate knowledge and awareness about the disease are crucial for further control of the severity of the disease [33][34][35][36][37]. There are few studies assessing the general public's knowledge and perception of migraines in the Kingdom of Saudi Arabia (KSA) [1,36]. However, most previous studies have revealed a poor level of knowledge and awareness of migraine in Saudi Arabia [1,36,38] and other countries [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation